Medical Management of Cerebral Vasospasm following Aneurysmal Subarachnoid Hemorrhage: A Review of Current and Emerging Therapeutic Interventions. (15th April 2013) - Adamczyk, Peter; He, Shuhan; Amar, Arun Paul; Mack, William J.
Abstract : Cerebral vasospasm is a major source of morbidity and mortality in patients with aneurysmal subarachnoid hemorrhage (aSAH). Evidence suggests a multifactorial etiology and this concept remains supported by the assortment of therapeutic modalities under investigation. The authors provide an updated review of the literature for previous and recent clinical trials evaluating medical treatments in patients with cerebral vasospasm secondary to aSAH. Currently, the strongest evidence supports use of prophylactic oral nimodipine and initiation of triple-H therapy for patients in cerebral vasospasm. Other agents presented in this report include magnesium, statins, endothelin receptor antagonists, nitric oxide promoters, free radical scavengers, thromboxane inhibitors, thrombolysis, anti-inflammatory agents and neuroprotectants. Although promising data is beginning to emerge for several treatments, few prospective randomized clinical trials are presently available. Additionally, future investigational efforts will need to resolve discrepant definitions and outcome measures for cerebral vasospasm in order to permit adequate study comparisons. Until then, definitive recommendations cannot be made regarding the safety and efficacy for each of these therapeutic strategies and medical management practices will continue to be implemented in a wide-ranging manner.